FGFR Inhibitor Ameliorates Hypophosphatemia and Impaired Engrailed‐1/Wnt Signaling in FGF2 High Molecular Weight Isoform Transgenic Mice. Issue 9 (2nd February 2016) - Du, Erxia; Xiao, Liping; Hurley, Marja M.
ABSTRACT: High molecular weight FGF2 transgenic (HMWTg) mouse phenocopies the Hyp mouse, homolog of human X‐linked hypophosphatemic rickets with hypophosphatemis, and abnormal FGF23, FGFR, Klotho signaling in kidney. Since abnormal Wnt signaling was reported in Hyp mice we assessed whether Wnt signaling was impaired in HMWTg kidneys and the effect of blocking FGF receptor (FGFR) signaling. Bone mineral density and bone mineral content in female HMWTg mice were significantly reduced. HMWTg mice were gavaged with FGFR inhibitor NVP‐BGJ398, or vehicle and were euthanized 24 h post treatment. Serum phosphate was significantly reduced and urine phosphate was significantly increased in HMWTg and was rescued by NVP‐BGJ398. Analysis of kidneys revealed a significant reduction in Npt2a mRNA in HMWTg that was significantly increased by NVP‐BGJ398. Increased FGFR1, KLOTHO, P‐ERK1/2, and decreased NPT2a protein in HMWTg were rescued by NVP‐ BGJ398. Wnt inhibitor Engrailed‐1 mRNA and protein was increased in HMWTg and was decreased by BGJ398. Akt mRNA and protein was decreased in HMWTg and was increased by NVP‐BGJ398. The active form of glycogen synthase 3 beta (pGSK3‐β) and phosphor‐β‐catenin were increased in HMWTg and were both decreased by NVP‐BGJ398 while decreased active‐β‐catenin in HMWTg was increased by NVP‐BGJ398. We conclude that FGFR blockade rescued hypophosphatemia by regulating FGF and WNT signaling in HMWTg kidneys. J. Cell. Biochem. 117: 1991–2000, 2016. © 2016 Wiley Periodicals, Inc. Abstract : This study examined the effect of short‐term blocking of FGFRs using NVP‐BGJ398 on phosphate homeostasis in kidneys of FGF2 high molecular weight isoform transgenic mice. FGFR inhibitor ameliorates hypophosphatemia and impaired Engrailed‐1/Wnt signaling in HMWTg mice.